Birthing parent perspectives on measuring the quality of perinatal care: metrics, timing, and process - Tully, Kristin P. (Frontiers in Health Services, 2024)
ObjectiveCentering birthing parents is critical for improving reproductive health policies and practices. This study investigates patient perspectives on measuring the quality of perinatal care.MethodsA cross-sectional qualitative research study was conducted at an academic medical center in the Southeastern United States. Individuals who had recently given birth participated in audio-recorded interviews between May 2020 and September 2020. This analysis addresses the research question, “If we were providing quality healthcare for families, how would we know?” Transcribed and translated responses were inductively coded to develop categories and identify themes.ResultsForty birthing parents participated in the study. Metrics, timing, and process were identified as important components of meaningfully measuring the quality of perinatal care. Recommended metrics included asking patients whether their health priorities were addressed. Additional metrics of importance were whether coping strategies were provided, the clarity of information provided, patient comprehension of health information, the extent to which care planning was collaborative among patients and their healthcare team members, whether clinicians alleviated patient doubts, patient feelings of being taken care of, healthcare team mannerisms, clinician demonstrations of respect for patient autonomy, and postpartum visit attendance. With regard to timing, patients desired that their healthcare team members “check-in” with them as part of an ongoing, direct dialog. Birthing parents also wanted opportunities to provide feedback soon after encounters. As part of a robust measurement process, they wanted to share their insights with someone who was not a part of their healthcare team, for maintaining confidentiality. The patients desired a “serious platform” with accessible methods for all birthing parents to be able to convey nuanced accounts of their care. They also wanted to hear from the healthcare institutions about their feedback. Birthing parents sought assurances for their perinatal care feedback to be de-identified to protect them from potential retaliation. The participants recognized that they might need to utilize healthcare services from the same institution and individuals in the future.ConclusionBirthing parents expressed desire for their perinatal healthcare experiences to be understood. Meaningful quality measurement may be promoted through transparent and multimethod opportunities for patients to securely share insights. In addition to healthcare systems communicating assurances of patient confidentiality, institutional feedback in response to patient-reported experiences is recommended.